A Pattern for Iron Ore Mines Financing - Mehdi Ali Hosseini; Mohammad Hashem Botshekan; Amir Hossein Mozayani; Moslem Peymanifurushani (Journal of Asset Management and Financing)
Acknowledging the lack of financial resources in the field of mining, researchers have found a solution in the use of new tools. Despite the existence of tools, the mining sector still lacks financial resources. Therefore, this research aims to provide a comprehensive solution, taking into account domestic and foreign theoretical and experimental background, to solve the problem of lack of financial resources in iron ore mines. For this purpose, this research firstly studies the available sources through theme analysis, the main themes including 48 basic themes, 10 organizing themes, and 3 comprehensive themes. It then extracts the conceptual model of the mining financing pattern in three levels of dimensions, components, and indicators. Then, this conceptual model, along with the solutions to improve the identified indicators, have been submitted to the expert survey using a questionnaire. The experts were selected by purposive sampling and their answers were analyzed by confirmatory factor analysis. Finally, the conceptual model and solutions obtained from the studies of this research were confirmed. The most important solutions have been presented to solve the budget deficit, adjust the policies of the central bank, manage risk, increase the efficiency of the industry, improve the rules and regulations, and make the institutions more efficient.Keywords: Financing Model, Mines, Iron Ore Mines, Iran. IntroductionDespite the existing capacity, Iran's mining industry has not been very successful. Benefiting from these large resources, as well as the availability of low-priced energy and a favorable labor force, the special regional position and the competitiveness of its products in the regional and world markets should be used to participate in this sector in international trade and markets. The necessary measures should be taken and sufficient facilities should be provided for it. Despite the investments made in the mining sector, this sector has not yet found its real position in the whole economy and there is a big gap between the existing capacities and the current situation.The field of mines and industries related to mining is one of the most important economic sectors of countries that are rich in mineral resources. This section has many previous and subsequent relationships that add to its importance. Until now, there has been some research on the financing of mines. But so far, no research has been done that specifically and accurately examines the problem of financing mines and provides a comprehensive solution or even explains the dimensions of this problem. Therefore, this research seeks to provide a comprehensive solution to improve the financing of iron ore mines. In this study, the theoretical foundations and background of the research has been discussed first. Then, presenting the summary of the findings in the primary studies in the section on theoretical foundations and background of the research, the method used in this research is described. After stating the research method, the findings of this study are stated and the conclusion is presented at the end.Materials and MethodsThe first step of this research was to collect data from existing documents, questionnaires, and interviews. Therefore, in the first stage, the data collection tool is document review and interview. At this stage, all materials related to the financing of mines, including financing methods, issues and problems, complications, special features of the mine that affect financing, and ways to improve the financing of mines were reviewed. In the second step, the information obtained from the previous step was analyzed through thematic analysis. By studying the texts, first, the themes are identified from the specification or concept of the studied text and then the category of the theme is determined based on its inclusion. Since these themes have been identified according to the researcher's opinion, to complete it, a table of themes was presented to the experts and they were interviewed through a semi-structured questionnaire. The content analysis of the interviews was done using MAXQDA software. At this stage, the final number of themes along with their class is concluded. In addition, based on the analysis of the output of this software, a conceptual model of mining financing was extracted, which shows all the components affecting the country's mining financing system.To validate the model, experts were asked through a researcher-made questionnaire. The answers to the questions were set on a Likert scale from one to five. After receiving the answers, quantitative analysis was done on the data. First, the validity and reliability of the questionnaire were checked, and after its confirmation, the evaluation of the structural part and the overall fit of the model was done using the method of confirmatory factor analysis. FindingsIn the qualitative part of the research, which is the first step, themes and classifications were obtained. These themes were identified in three levels dimensions, components, and indicators. The next step is to show the relationship between the identified themes. Since the results of studies and interviews were entered into the MAXQDA software from the beginning, this software was also used to show the network of identified themes. By using the overarching, organized, and basic themes identified and the relationships discovered by the software, the obtained conceptual model can be presented as follows: Figure 1: The conceptual modelKolmogorov-Smirnov test was used to check the normality of the distribution of variables. Considering that the significance level of the distribution of variables is less than 5% (non-normal); therefore, SmartPLS software has been used for analysis. In addition to Cronbach's alpha method, the reliability of the questions was evaluated using the methods of coefficient of factor loadings, significance of factor loadings, composite reliability, shared reliability, and rho_A reliability, and all of them confirmed the reliability. The validity of the questions was also investigated using the face validity method, divergent validity using two Fornell-Larker methods, and mutual factor loadings, all of which indicated the validity of the questions. The evaluation of the structural part of the model has been done with the R2 criterion. The endogenous structures of the model with a value of more than 0/74 have a strong structural relationship, and this indicates the strength of the structural part of the model. To evaluate the confirmatory factor analysis model, the second root index of the estimation of the variance of the approximation error has been used. According to Joseph et al. (2017), the limit of this index is 0.1. For the model, the value of this index is equal to 0.078, less than the value of 0.1, and one can say that the model has a good fit with the factor structure and the theoretical foundation of the research. On the other hand, according to the opinion of Ringle and Sarstedt (2016), the acceptable value is less than 0/08 and it is also acceptable from this point of view. Discussion and ConclusionsBased on the findings, it can be said that the model has a good fit with the factor structure and the theoretical foundation of the research; therefore, the initial conceptual model is confirmed. In addition to confirming the model, experts were asked about financing solutions for iron ore mines. These solutions have been obtained from primary research studies on existing documents and interviews. In the following, the opinions of the experts obtained from the analysis of the information obtained from the questionnaires has been summarized. Freeing the price of energy carriers of mining companies and allocating it to mining sector development projects will improve the financing of iron ore mines. Providing tax incentives and reducing export duties on iron ore products will make it easier to finance iron ore mines. The policy of the central bank should move towards the liberalization of the exchange rate in the pricing of mineral products. Accepting a mining license as an acceptable collateral with banks can help finance iron ore mines through the banking network. The initial stages of mine development, i.e. mine exploration, are associated with risk. According to the information obtained, this risk is one of the most fundamental obstacles to the financing and development of mines, including iron ore mines. If this obstacle is removed or shortened, the entry of financial resources into this industry will increase. The more efficient the mines are, the easier it will be to finance them. Profit is one of the most basic elements of financial statements that has always been taken into consideration and is referred to as a measure to evaluate the continuity of activity and efficiency. The laws need to be reviewed with a comprehensive view in line with the development of the country's mines. In revising the laws, attention should be paid to strengthening the monitoring of mineral activities and licenses in the Mining Law and its executive regulations. According to the findings, the effectiveness of the Ministry of Health in financing iron ore mines has been low so far. Therefore, this important organization should take measures to have a greater impact on this market. The technical and financial empowerment of the geological organization in order to prepare, produce, and publish accurate and reliable geological information can improve the financing of iron ore mines.